1996
DOI: 10.1046/j.1365-313x.1996.9050659.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of auxin on the establishment of bilateral symmetry in monocots

Abstract: SummaryTo study the influence of auxin on the shift from radial to bilateral symmetry during monocot embryogenesis, the fate of young wheat (Triticurn aestivum L.) zygotic embryos has been manipulated in vitro by adding auxins, an auxin transport inhibitor and an auxin antagonist to the culture medium. The two synthetic auxins used, 2,4-dichlorophenoxyacetic acid (2,4-D) and 2,4,5-trichlorophenoxyacetic acid (2,4,5-T), induced identical phenotypes. In the most severe cases, the shift from radial to bilateral s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
65
0
3

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(74 citation statements)
references
References 24 publications
6
65
0
3
Order By: Relevance
“…However, conversion of these embryos into plants did not occur, probably due to a lack of development of the shoot apical meristem. Similar results were obtained by Lee et al (1997) with banana somatic embryos, and Nickle & Yeung (1993) with Daucus carota L.. Fischer & Neuhaus (1996) observed that the shoot apex development of Triticum aestivum L.. induced in 2,4,5-T was interrupted due to the vacuolization of the cells in the meristem. According to these authors, the establisment of polarity represents the initial stage of development of embryonic structures in monocots: the embryonary axis and the scutellum.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…However, conversion of these embryos into plants did not occur, probably due to a lack of development of the shoot apical meristem. Similar results were obtained by Lee et al (1997) with banana somatic embryos, and Nickle & Yeung (1993) with Daucus carota L.. Fischer & Neuhaus (1996) observed that the shoot apex development of Triticum aestivum L.. induced in 2,4,5-T was interrupted due to the vacuolization of the cells in the meristem. According to these authors, the establisment of polarity represents the initial stage of development of embryonic structures in monocots: the embryonary axis and the scutellum.…”
Section: Resultssupporting
confidence: 87%
“…Auxin polar transport in the globular embryo is essential for the establishment of polarity (Liu et al 1993). Polarity can be affected if auxin is evenly distributed in the embryo tissues due to an increase in the auxin endogenous level, which can occur by the application of endogenous auxin through the culture medium (Fischer & Neuhaus 1996).…”
Section: Resultsmentioning
confidence: 99%
“…For example, manipulation of the amount and spatial distribution of auxin (Liu et al 1993;Fischer and Neuhaus 1996;Hadfi et al 1998) in developing zygotic embryos phenocopies development observed in a number of embryo defective mutants (Mayer et al 1991). Many em-bryo-patterning mutants have altered auxin sensitivities or are associated with auxin signal transduction (Hardtke and Berleth 1998;Hammann et al 1999;Hobbie et al 2000) beginning as early as the primary zygotic division.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from wheat (Triticum aestivum) zygotic embryos indicate that heterogeneous auxin distribution plays an analogous role in monocot embryonic pattern formation (Fischer and Neuhaus, 1996;Fischer-Iglesias et al, 2001).…”
mentioning
confidence: 99%